1987
DOI: 10.1177/088740348700200404
|View full text |Cite
|
Sign up to set email alerts
|

Danger To Police During Domestic Encounters: Assaults On Baltimore County Police, 1984-86

Abstract: How dangerous are domestic encounters to police officers? This question, posed by police, policymakers, and researchers, has been answered through anecdotes and assumptions, and more recently by empirical data. But the findings have been mixed. Police training manuals have focused on the danger of family disputes, citing high figures reported by the FBI of law enforcement officers killed. Researchers on family violence (Straus, et al., 1980), violent police-citizen encounters (Lester, 1980), and police respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 5 publications
3
31
2
1
Order By: Relevance
“…Here again, most of the incidents began immediately upon the arrival of the officers or shortly thereafter, resembling the ambush situation previously discussed, not the investigative stages of the police response. Some critics, however, have argued that while police fatalities may be relatively rare, assaults may be a significant source of injury for police officers in domestic violence cases (Uchida, Brooks, & Kopers, 1987).…”
Section: Domestic Violence Cases Are Extraordinarily Dangerous For Pomentioning
confidence: 99%
“…Here again, most of the incidents began immediately upon the arrival of the officers or shortly thereafter, resembling the ambush situation previously discussed, not the investigative stages of the police response. Some critics, however, have argued that while police fatalities may be relatively rare, assaults may be a significant source of injury for police officers in domestic violence cases (Uchida, Brooks, & Kopers, 1987).…”
Section: Domestic Violence Cases Are Extraordinarily Dangerous For Pomentioning
confidence: 99%
“…K. Meyer, Magedanz, Dahlin, & Chapman, 1981;C. K. Meyer, Magedanz, Kieselhorst, & Chapman, 1979;Stobart, 1972;Uchida, Brooks, & Kopers, 1987;L. A. Wilson, Brunk, & Meyer, 1990;.…”
Section: Introductionmentioning
confidence: 96%
“…Subsequent research set out to find the most dangerous calls for service that the police respond to (Ellis et al, 1993;Garner & Clemmer, 1986;Hirschel, Dean, & Lumb, 1994;Stanford & Mowry, 1990;Uchida et al, 1987). Stanford and Mowry (1990), for example, examined 791,837 calls for service received by Tampa police in 1989 and observed that domestic calls were less likely than general disturbance calls to result in assaults to officers, but more likely to result in injuries.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations